Deceptive sustainability: Cognitive bias in people's judgment of the benefits of CO2 emission cuts. (August 2019) - Holmgren, Mattias; Kabanshi, Alan; Langeborg, Linda; Barthel, Stephan; Colding, Johan; Eriksson, Ola; Sörqvist, Patrik
Abstract: People's beliefs in the actions necessary to reduce anthropogenic carbon dioxide (CO2 ) emissions are important to public policy acceptability. The current paper addressed beliefs concerning how periods of small emission cuts contribute to the total CO2 concentration in the atmosphere, by asking participants to rate the atmospheric CO2 concentration for various time periods and emission rates. The participants thought that a time period with higher emission rates combined with a period of lower emission rates generates less atmospheric CO2 in total, compared to the period with high emission rates alone – demonstrating a negative footprint illusion (Study 1). The participants appeared to base their CO2 estimates on the average, rather than on the accumulated sum, of the two periods' emissions – i.e. an averaging bias (Study 2). Moreover, the effect was robust to the wordings of the problem presented to the participants (Study 3). Together, these studies suggest that the averaging bias makes people exaggerate the benefits of small emission cuts. The averaging bias could make people willing to accept policies that reduce emission rates although insufficiently to alleviate global warming. Highlights: Atmospheric accumulation of CO2 is estimated to decrease when emission cuts are made. A period of high emissions was thought to be compensated by a lower emission period. This negative footprint illusion seems to be caused by an averaging bias.